Financial performance indicators in Lebanese hospitals: a sustainable improvement strategy - Alaaraj, Hassan; Aoun, Malak (CSRC Publishing, 2016)
Although the quality of healthcare services has been measured extensively using different approaches however; the financial approach is considered one of the most tangible indicators to evaluate the effectiveness of the implied quality improvement strategies at the Lebanese hospitals. It is essential to measure quality of performance especially when hospitals are competing for accreditation and sustainability. Therefore, this paper highlights the significant key performance indicators applied by the Lebanese hospitals and mainly the financial performance indicators to improve the healthcare financing in Lebanon.Such financial metrics are found critical for hospitals to define and evaluate their performance especially in terms of insurance and financial coverage. This paper demonstrates conceptually the current strategies for improving the healthcare financing system in Lebanon yet, future studies are encouraged to provide analytical elaborations for the financial status and relative performance indicators of the healthcare system in Lebanon.